Risk factors for new onset and persistence of multi-site musculoskeletal pain in a longitudinal study of workers in Crete. Issue 1 (3rd August 2012) - Solidaki, Eleni; Chatzi, Leda; Bitsios, Panos; Coggon, David; Palmer, Keith T; Kogevinas, Manolis
Abstract : Objectives: To explore occupational and psychological risk factors for the incidence and persistence of multi-site musculoskeletal pain. Methods: We conducted a longitudinal investigation of three occupational groups in Crete, Greece. Baseline information was obtained at interview about pain in the past year at each of six anatomical sites, and about possible risk factors for subsequent symptoms. Twelve months later, subjects were re-interviewed about pain at the same anatomical sites in the past month. Pain at two or more sites was classed as multi-site. Associations with new development and persistence of multi-site pain at follow-up were assessed by logistic regression. Results: Analysis was based on 518 subjects (87% of those originally selected for study). At follow-up, multi-site pain persisted in 217 (62%) of those who had experienced it in the year before baseline, and was newly developed in 27 (17%) of those who had not. Persistence of multi-site pain was significantly related to physical loading at work, somatising tendency and beliefs about work as a cause of musculoskeletal pain, with OR (95% CI) for the highest relative to the lowest exposure categories of 2.3 (1.0 to 5.6), 2.6 (1.5 to 4.6) and 1.9 (1.1 to 3.3) respectively. Development of new multi-site pain was most strongly associated with working for ≥40 h per week (OR 5.0, 95% CI 1.1 to 24.0). Conclusions: Our findings confirm the importance of both physical loading at work and somatising tendency as risk factors for multi-site pain, and suggest that persistence of pain is also influenced by adverse beliefs about work causation.